The development of social values in childhood and early adolescence: A systematic review - Murcia-Álvarez, E.; Tendais, I.; Ramos, A.; Rodrigues, R. B.; Costa, L. P. da.; Cavadas, M.; Marques, S.; Ramos, V.; Correia, I. (Children and Youth Services Review, 2026)
Values are central to human social life. As conceptualised in Schwartz’s (1992) Theory of Basic Human Values, they are core to a person’s self-concept and drive individual actions towards both personal development and social transformation. Although, cross-cultural research with adults shows a consensus regarding value structure and priorities, research with young populations is still very recent. In this paper, we systematically review studies on the development of basic human values in childhood and early adolescence (5 to 14 years old) and synthesise evidence regarding the fit of children’s and adolescents’ values to the theoretical structure, the development of value hierarchy and importance from childhood to early adolescence. The review was conducted according to the PRISMA guidelines and a final set of 45 papers was included. The evidence provides extensive support for Schwartz’s theoretical model in childhood and early adolescence. A highly differentiated value structure was found in most studies from several countries, providing great support for the universal nature of values. Moreover, the identified patterns of value change support the motivational compatibilities and oppositions of the model and suggest that values become more stable with age.